Abdominal morbidity after single- versus double-pedicled deep inferior epigastric perforator flap use. Issue 9 (September 2016) - Uda, Hirokazu; Tomioka, Yoko Katsuragi; Sarukawa, Syunji; Sunaga, Ataru; Kamochi, Hideaki; Sugawara, Yasusih; Yoshimura, Kotaro
Summary: Background and aim: The reduced incidence of donor site morbidity after deep inferior epigastric perforator (DIEP) flap is because the rectus muscle and its fascia are preserved. However, no study has proved that trunk flexion recovers not by the compensatory effect of the contralateral rectus muscle but by reinnervation of the ipsilateral rectus muscle. We hypothesized that if sufficient reinnervation occurs, patients who undergo single-pedicled DIEP (S-DIEP) flap or double-pedicled DIEP (D-DIEP) flap breast reconstruction would have similar levels of preoperative trunk flexion. To determine this, we investigated perioperative changes in trunk flexor muscle ability quantitatively using an isokinetic dynamometer in patients who had received S-DIEP or D-DIEP. Methods: Patients who underwent breast reconstruction with S-DIEP ( n  = 37) and D-DIEP ( n  = 30) were included in this study. Pre- and postoperative trunk flexor muscle ability was measured prospectively by an isokinetic dynamometer in all patients. Postoperative abdominal pain and stiffness, patients' activity, and incidence of bulging were also investigated. Results: Six months after surgery, the trunk flexor muscle ability recovered and did not significantly decrease subsequently in either group. This finding was consistent with the result that patients' activities and the incidence of bulging were similar between the two groups. Conclusions: Our results show that reinnervation of the rectus muscle can be confirmed at 6 months after DIEP flap elevation. Thus, we recommend D-DIEP flap without concern for abdominal wall weakness, especially in patients with multiple abdominal scars and who require breast tissue exceeding the amount of tissue that can be transferred with S-DIEP flap.